Determination of Cell Wall Protein from Selected Feedstuffs and its Relationship with Ruminal Protein Digestibility in Vitro - Anuraga Jayanegara; S. P. Dewi; N. Laylli; E. B. Laconi; Nahrowi Nahrowi; M. Ridla (Faculty of Animal Science, Bogor Agricultural University, 2016)
This study was aimed to analyze neutral detergent insoluble crude protein (NDICP) and acid detergent insoluble crude protein (ADICP) contents of various commonly used forage and concentrate feedstuffs in Indonesia. A number of forages and concentrates, i.e. gliricidia, trichantera, indigofera, calliandra, papaya leaves, cassava leaves, leucaena, rapeseed meal, corn gluten feed, soybean meal, copra meal, palm kernel meal, fish and bone meal and wheat bran were subjected to proximate analysis, cell wall nitrogen determination and in vitro rumen fermentation evaluation. Chemical composition analysis was done in duplicate. The in vitro incubation was conducted in 14 treatments and 3 replicates by following a randomized complete block design. Variables measured after the incubation were total volatile fatty acid (VFA), ammonia, dry matter digestibility (DMD), organic matter digestibility (OMD) and crude protein digestibility (CPD). Results revealed that among the forages, cassava leaf had the highest proportion of NDICP while corn gluten feed was the highest among the concentrates. Different from that of NDICP, the highest proportion of ADICP was obtained in papaya leaf and copra meal for the forages and concentrates, respectively. Higher proportion of NDICP tended to decrease CPD (P<0.1). Although higher ADICP apparently tended to decrease CPD as well, the relationship was insignificant due to the higher variation of the dependent variable. It was concluded that cell wall protein proportion in feed may be used as an indicator to determine the quality of protein and its utilization in the rumen.